Crystal Structure of an Indole-3-Acetic Acid Amido Synthetase from Grapevine Involved in Auxin Homeostasis([W]) - Peat, Thomas S. (American Society of Plant Biologists, 2012)
Auxins are important for plant growth and development, including the control of fruit ripening. Conjugation to amino acids by indole-3-acetic acid (IAA)-amido synthetases is an important part of auxin homeostasis. The structure of the auxin-conjugating Gretchen Hagen3-1 (GH3-1) enzyme from grapevine (Vitis vinifera), in complex with an inhibitor (adenosine-5′-[2-(1H-indol-3-yl)ethyl]phosphate), is presented. Comparison with a previously published benzoate-conjugating enzyme from Arabidopsis thaliana indicates that grapevine GH3-1 has a highly similar domain structure and also undergoes a large conformational change during catalysis. Mutational analyses and structural comparisons with other proteins have identified residues likely to be involved in acyl group, amino acid, and ATP substrate binding. Vv GH3-1 is a monomer in solution and requires magnesium ions solely for the adenlyation reaction. Modeling of IAA and two synthetic auxins, benzothiazole-2-oxyacetic acid (BTOA) and 1-naphthaleneacetic acid (NAA), into the active site indicates that NAA and BTOA are likely to be poor substrates for this enzyme, confirming previous enzyme kinetic studies. This suggests a reason for the increased effectiveness of NAA and BTOA as auxins in planta and provides a tool for designing new and effective auxins.